Revitalizing external audit in the era of society 5.0: leveraging artificial intelligence for human-centered progress - Kumala, Chintya Anindita; Sudiyono, Widhiyo (Universitas Muhammadiyah Malang, 2025)
Purpose: This article summarizes a literature review that discusses the role of AI in various aspects of external auditing, such as improving external audit quality, external audit process efficiency, and fraud detection. The literature emphasizes the importance of applying AI technologies in changing the external audit landscape, offering benefits such as in-depth data analysis, time efficiency, and cost reduction in the external audit process. This article also explains how the development of AI and other technologies impacts the transformation of society, especially in the context of Society 5.0, which emphasizes the integration of technology to improve human well-being. Methodology/approach: This article presents a review of various research materials that address the role of artificial intelligence (AI) in the context of external auditing, based on the literature review research method. Findings: The use of AI in external auditing demonstrates how technology can be used to improve the efficiency, accuracy, and relevance of external audits, in line with the vision of a better society championed in Society 5.0. Practical implications: This study highlights AI's crucial role in enhancing external auditing by improving quality, efficiency, and accuracy, offering practical insights for audit firms to streamline processes, reduce errors, and adapt to technological advancements in the era of Society 5.0. Originality/value: This article contributes to the literature by exploring the broader societal implications of AI in external auditing within the context of Society 5.0, highlighting its role in not only enhancing audit quality but also promoting ethical and social dimensions aligned with the goals of this technology-driven framework.